Crafting the Artist: Franz Kafka and Disciplinary Violence (Konturen, 2026)
This essay examines Kafka’s chronic struggle with writer’s block from the perspective of disciplinary violence, and uses it to expand on Dungey’s thesis, that Kafka saw writing as a means of creating an artistic subjectivity. By studying Kafka’s letters and diaries it becomes clear that Kafka saw writing as in inherently violent act that was capable of maintaining a dialectical tension between his ‘real’ and ‘artistic’ selves, and this raises the question of whether his suffering was warranted. Through a reading of In the Penal Colony, we can see how Kafka explored this dilemma in his own writing, and how it resulted in a loss of authorial control over the symbolic nature of the text.
Keywords: Kafka; Foucault; Nietzsche; power; discipline; subjectivity; violence